Morphological and Histological Analysis of the Gastrointestinal Systems in Triplophysa strauchii and Triplophysa tenuis: Insights into Digestive Adaptations - Zhengwei Wang; Lirong Zhang; Jie Wei; Huimin Hao; Syeda Maira Hamid; Shixin Gao; Wenjun Li; Zhulan Nie (Animals)
Fish are vital for material cycling and energy flow in aquatic ecosystems. The genus Triplophysa, with over 100 known species, is significant in the Central Asian highlands’ freshwater ecosystems. T. strauchii and T. tenuis, as representatives, occupy distinct ecological niches and face challenges from climate change and human activities. There is a lack of research on Triplophysa fishes’ digestive systems, especially comparative studies, so this research aims to fill this gap. In September 2024, 40 samples of T. strauchii were collected from Sayram Lake and 40 samples of T. tenuis were collected from the Muzat River in Xinjiang. After acclimation, morphological observations (measuring fish and digestive tract parameters) and histological analyses (paraffin sectioning, HE staining, and microscopy) were carried out. The data were sorted in Excel and analyzed with an independent samples t-test in SPSS 27.0. Morphologically, T. strauchii has an obtuse snout, terminal mouth, specific upper lip papillae, and an S-shaped intestine about (1.45 ± 0.11) times its body length, while T. tenuis has an arc-shaped subterminal mouth, fringed papillae, and a spiral-shaped intestine around (0.82 ± 0.09) times its body length. Both possess a digestive tract, glands, and a hepatopancreas attached to the mesentery. Histologically, a large number of club cells were found in the oropharyngeal cavities of both species; their secretions have an adhesive effect on food, aiding food selection. Their digestive systems vary in structure and cell composition: the oropharyngeal cavity has three layers; the esophagus has four layers with more goblet cells in T. strauchii; the stomach has three regions without goblet cells and a thicker muscular layer in T. strauchii; the intestinal wall has four layers with different villi and goblet cell distributions; the hepatopancreas has lobules; and T. strauchii has a typical portal area. In conclusion, this study systematically compared the gastrointestinal systems of T. strauchii and T. tenuis for the first time, revealing significant structural differences related to their niches and feeding patterns as adaptations to specific environments. It fills the research gap, provides a basis for exploring fish ecological adaptation and environmental impacts on digestion, offers new ideas for Triplophysa protection strategies, and guides fish evolutionary biology research and Triplophysa resource protection and utilization.